Keanekaragaman Jenis Rayap Tanah dan Dampak Serangan Pada Bangunan Rumah di Perumahan Kawasan Mijen Kota Semarang - Annisa Savitri; Martini Martini; Sri Yuliawati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Termite attacks on buildings construction in Indonesia has become a major problem since the beginning until now, so that termites are known as pests. The residential development has after the habitats of termites that an impact on the narrowing of the environmental termites and reduce termite food source. So this led to the increasing of a termite attack. This research was conducted at kawasan Mijen Kota Semarang. The objectives of this research are to identify the type of subterranean termites and to know the impact of subterranean termites attack on house building. This research is descriptive with survey method and cross sectional approach. The samples in this study are building houses using purposive sampling and taking termite using accidental sampling technique. The result of this study showed that the termite species Macrotermes gilvus Hagen soldiers (71%) and Coptotermes curvignathus Holmgren (29%). The type of a house component that usually suffered a lot of damage is the door frame with the intensity (minimum damage). Therefore, it is necessary to attempt an anti-termite treatment for houses, to repair the damage building components immediately, to clean the wood, the trees that have died or other lignoselulosa material which related to the soil.